A spatial difference-in-difference approach to study the impact of Punggol Digital District hub on property values - Fan, Guan Fung (Nanyang Technological University, 2023)
In recent years, Singapore has announced multiple large-scale development plans, such as the Punggol Digital District (PDD), Woodlands Regional Centre, and the Jurong Lake District. These demarcated districts aim to create new job opportunities and residential buildings while enabling individuals to work close to their homes, reflecting Singapore’s development from a monocentric city into a polycentric city. While many studies in Singapore model housing prices, there remains a research gap on how decentralisation affects the prices of the surrounding housing properties.